1998
DOI: 10.1177/0263276498015003011
|View full text |Cite
|
Sign up to set email alerts
|

Love and Structure

Abstract: Is romantic love a particularly Western and modern phenomenon, as many social theorists argue, or a universal experience, as sociobiologists claim? This article argues that both these approaches err in taking sexual attraction as the essential characteristic of romance, whereas historical and personal accounts stress idealization of a particular other. Romantic love is properly defined as an experience of transcendence and is elaborated in cultural configurations of three basic types. The first is in hierarchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…"Sex" and "passion" fit with most of the definitions of romantic love that acknowledge the erotic/passionate aspect of romantic love (Sternberg, 1988(Sternberg, , 1996(Sternberg, , 2006, in his triangular theory of love posits passion as one vertex; Berscheid & Meyers, 1996;Berscheid & Regan, 2005, posit that love is a synthesis of companionate and passionate feelings). "Mutual" and "equality" fit with Lindholm's (1998aLindholm's ( , 1998b) discussion on the importance of equal status as a precipitating condition and attribute of romantic love, as well as de Korotayev's (1999) andde Munck et al's (2010) findings that romantic love, as a criterion for marriage, is causally related to an increase in female status and intimacy. While Sternberg views intimacy as a second vertex, he does not reflect on an assessment of mutuality as a necessary condition for intimacy.…”
Section: Examining Freelist Datasupporting
confidence: 60%
See 1 more Smart Citation
“…"Sex" and "passion" fit with most of the definitions of romantic love that acknowledge the erotic/passionate aspect of romantic love (Sternberg, 1988(Sternberg, , 1996(Sternberg, , 2006, in his triangular theory of love posits passion as one vertex; Berscheid & Meyers, 1996;Berscheid & Regan, 2005, posit that love is a synthesis of companionate and passionate feelings). "Mutual" and "equality" fit with Lindholm's (1998aLindholm's ( , 1998b) discussion on the importance of equal status as a precipitating condition and attribute of romantic love, as well as de Korotayev's (1999) andde Munck et al's (2010) findings that romantic love, as a criterion for marriage, is causally related to an increase in female status and intimacy. While Sternberg views intimacy as a second vertex, he does not reflect on an assessment of mutuality as a necessary condition for intimacy.…”
Section: Examining Freelist Datasupporting
confidence: 60%
“…For instance, "being together" and "connection" fit with criteria of romantic love proposed by most sociologists or psychologists, particularly those who emphasize a "Platonic model of romantic love" that Kövecses (1987, p. 18) has identified as the "dominant metaphor" of romantic love in the United States (see also Lindholm, 1998aLindholm, , 1998bSinger, 1987Singer, , 1994Soble, 1990;Tennov, 1979). "Sex" and "passion" fit with most of the definitions of romantic love that acknowledge the erotic/passionate aspect of romantic love (Sternberg, 1988(Sternberg, , 1996(Sternberg, , 2006, in his triangular theory of love posits passion as one vertex; Berscheid & Meyers, 1996;Berscheid & Regan, 2005, posit that love is a synthesis of companionate and passionate feelings).…”
Section: Examining Freelist Datamentioning
confidence: 90%
“…The finding that passionate love is present in some form or another in most cultures around the globe (Jankowiak & Paladino, 2008;Jankowiak & Fisher, 1992) has produced a cottage industry of case studies exploring the ethnographic and theoretical implications of this new-found human universal (Ahearn, 2001;Cole & Thomas, 2009;Constable, 2003;De Munck & Korotayev, 2007;Hirsch & Wardlow, 2006;Lindholm, 1998a;Padilla, Hirsch, Munoz-Laboy, Sember, & Parker, 2007;Swidler, 2001). Psychologists working within a different conceptual framework have explored the meanings and embedded assumptions that Americans associate with being in the state of love (Berscheid, 2006;Dion & Dion, 2010;Gao, 2001;Fehr, 1994;Goodwin & Findlay, 2005;Hatfield, Rapson, & Martel, 2007;Hendrick & Hendrick, 1986;Kline, Horton, & Zhang, 2008;Lee, 1988;Riela, Rodriguez, Aron, Xu, & Acevedo, 2010;Tennov, 1979;Xu et al, 2011;Ze'ev, 2004;Zeki & Romaya, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Jankowiak and Fischer (1992) write that for romantic love to be present the other must be ''idealized. '' For Lindholm (1998, 1995, a critic of the idea that romantic love is a cultural universal, the kernel feature of romantic love is a feeling of transcendence that comes from perceiving the other, and the relationship, as unique. Gottschall and Nordlund (2006) describe the importance of both intimacy and idealization when, in their cross-cultural analysis of texts of oral folktales on romantic love, they begin their article by noting that to be in love .…”
mentioning
confidence: 99%